PENGARUH MODEL PEMBELAJARAN INKUIRI DAN MOTIVASI BELAJAR TERHADAP PEMAHAMAN KONSEP IPA - Soma Putra, Ida Bagus (Universitas Pendidikan Ganesha, 2012)
Abstract: The Effect of Inquiry Model of Teaching and Learning Motivation onthe Comprehension of Science Concepts. This study was aimed at (1) describing thedifference in the comprehension of science concepts between the students who learnedthrough inquiry teaching model and those who learned through conventional model ofteaching, (2) describing the difference in the comprehension of science conceptsbetween the students with high learning motivation and those with low learningmotivation, and (3) describing the interactive effect between inquiry model of teachingand conventional model of teaching on the students? comprehension of scienceconcepts. The population consisted of all the fifth grade students at SD No. 3BanjarJawa and SD Lab Undiksha Singaraja in the school year 2011/2012. The samplesize was 76 students. The data in this study consisted of (1) the data on the students?learning motivation, (2) the data on comprehension of science. The data were analyzedusing descriptive statistics and 2x2 factorial ANACOVA. The results showed that (1)there was a difference in the achievement in the comprehension of scienceconceptsbetween the students who learned through the inquiry model of teaching andthose who learned through the conventional model of teaching (F=8.238; P<0.05). theinquiry model of teaching yielded a higher level in the comprehension of scienceconcepts than the conventional model of teaching; (2) there was a difference in theachievement in the comprehension of science concepts between the students with highlearning motivation and those with low learning motivation (F=7.372;P<0.05), thestudents with high learning motivation had a higher level of comprehension of scienceconcepts than those with low learning motivation; and (3) there was an interactive effectbetween the inquiry model of teaching and learning motivation on the students?achievement in the comprehension of science concepts (F=24.302;P<0.05).Abstrak: Pengaruh Model Pembelajaran Inkuiri dan Motivasi Belajar TerhadapPemahaman Konsep IPA. Penelitian ini bertujuan: (1) mendeskripsikan perbedaanpemahaman konsep IPA antara siswa yang belajar dengan model pembelajaran inkuiridengan siswa yang belajar dengan model pembelajaran konvensional, (2)mendeskripsikan perbedaan pemahaman konsep IPA antara siswa yang memilikimotivasi belajar tinggi dengan siswa yang memiliki motivasi belajar rendah, dan (3)mendeskripsikan pengaruh interaktif antara model pembelajaran inkuiri dan modelpembelajaran konvensional dengan motivasi belajar siswa terhadap pemahaman konsepIPA. Populasi penelitian ini adalah seluruh siswa kelas V SD Nomor 3 Banjar Jawa danSD Lab Undiksha Singaraja tahun pelajaran 2011/2012. Jumlah sampel dalampenelitian ini adalah 76 siswa. Data yang dikumpulkan adalah (1) data motivasi belajar2siswa, (2) data pemahaman konsep IPA. Data dianalisis dengan menggunakan statistikdeskriftif dan ANACOVA faktorial 2×2. Hasil penelitian menunjukkan bahwa: (1)terdapat perbedaan pemahaman konsep IPA yang dicapai antara siswa yang belajardengan model pembelajaran inkuiri dan siswa yang belajar dengan model pembelajarankonvensional (F= 8,238; P<0,05), model pembelajaran inkuiri menunjukkanpemahaman konsep IPA yang lebih baik dibandingkan dengan model pembelajarankonvensional. (2) Terdapat perbedaan pemahaman konsep IPA yang dicapai antarasiswa yang memiliki motivasi belajar tinggi dan siswa yang memiliki motivasi belajarrendah (F= 7,372; P<0,05), motivasi belajar tinggi menunjukkan pemahaman konsepIPA yang lebih baik dibandingkan motivasi belajar rendah. (3) Terdapat pengaruhinteraktif antara model pembelajaran inkuiri dengan motivasi belajar terhadappemahaman konsep IPA yang dicapai siswa (F= 24,302; P<0,05).Kata kunci: model pembelajaran inkuiri, motivasi belajar, pemahaman konsep